Analysis of Spectrum Vibration on Motor Cooling Tower at PT. X - Wibawaputra, Dhimas Rizky Anugrah; Gunadi, Gun Gun Ramdlan; Santoso, Budi (Jurnal Poli-Teknologi, 2024)
Vibration monitoring is one of the Condition Based Maintenance methods currently widely applied in industry to ensure asset reliability which aims to determine the actual condition status of the machine and to detect potential problems before damage occurs. Vibration values at the Drive End (DE) and Non-Drive End (NDE) of the cooling tower motor as a fan drive in conditions vibration causes damage based on ISO 10816-3. The results of spectrum analysis of high amplitude at 1X and some 2X and 3X on the axial side indicate that the cause of vibration is misalignment. After the repair, there is a decrease in the vibration value of the DE and NDE motor parts on the axial side from 14.7 mm/s and 12.4 mm/s to 2.3 mm/s and 2.6 mm/s so that it is said to be able to operate long-term.